Controllable fabrication and characterization of hydrophilic PCL/wool keratin nanonets by electronetting. (January 2017) - Zhu, Huihui; Li, Rong; Wu, Xingle; Chen, Ke; Che, Jiangning
Graphical abstract: Highlights: Keratin extracted from wool byl -cysteine redox method. One-step electronetting of Poly (ε-caprolactone) (PCL) and wool keratin. Nanofibers in diameter of 299–624 nm and dense nanonets in diameter of 25 ± 5 nm. With the addition of keratin, the water contact angles decreased around 20–50 degree. Abstract: Keratin wastes are an important source of renewable raw material. Regenerated wool keratin is a promising natural material for tissue engineering. In the present study, l -cysteine redox method was performed to extract keratin from wool and the nanonets fabricated by one-step electrospinning of Poly (ε-caprolactone) (PCL) and wool keratin were presented here. The resulting nanofiber mats showed two parts of structures: randomly oriented nanofibers in diameter of 299–624 nm and dense nanonets in diameter of 25 ± 5 nm. The forming and coverage of nanonets was mainly affected by the addition of wool keratin and the relative humidity. With the addition of keratin, the hydrophilic nanonets can be successfully fabricated, where the water contact angles decreased around 20–50 degree compared to that of the pure PCL nanofibers.